Back to basics: A re-evaluation of the relevance of imprinting in the genesis of Bowlby’s attachment theory - Robledo, Juan-Pablo; Cross, Ian; Boada-Bayona, Luisa; Demogeot, Nadine (Frontiers in psychology, 2022)
Attachment theory is one of the key theoretical constructs that underpin explorations of human bonding, taking its current form in John Bowlby’s amalgamation of ideas from psychoanalysis, developmental psychology and ethology. Such a period of interdisciplinary exchange, and Bowlby’s interest in Lorenz’ concept of imprinting in particular, have been subject to rather historical and biographical studies, leaving a fine-grained theoretical scrutiny of the exact relationship between imprinting and attachment still pending. This paper attempts to remedy such an omission by exploring the relationships between these two constructs. It critically reviews the theories of imprinting in general, of human imprinting in particular, and of attachment; analysis of the links between these processes bring to the foreground the distinction between supra-individual vs. individual aspects of bonding, the relevance of ‘proto-attachment’ phases before ‘proper’ Bowlbyan attachment is attained, and the role of communicative signals during such early phases. The paper outlines potential benefits of considering such elements in the study of early social cognition, particularly in respect of the study of the gaze and the infant-directed communicative register.